2017
DOI: 10.1007/s10096-017-2981-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of gastrointestinal pathogens in oncology patients by highly multiplexed molecular panels

Abstract: We compared the frequency of gastrointestinal (GI) pathogen detection in an oncology patient population by two multiplexed molecular assays, the Luminex xTAG® GI Pathogen Panel (GPP, which identifies 14 GI pathogens) and the BioFire GI pathogen panel (BFGP, which identifies 22 GI pathogens). We additionally reviewed the clinical characteristics of patients tested with both panels. A total of 200 prospectively collected and 81 archived stool samples were tested by both panels. In the prospective cohort, the GPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…3 ). Interestingly, these taxa are commonly found in patients with CRC 57 , with the Fusobacterium genus frequently being associated with tumor progression 58 . Moreover, CpT samples possessed microbial genera commonly involved in development of intestinal disease or pathologies, such as Streptococcus (taxonomic trend prevalence of 80.00% in CpT) and Gemella (taxonomic trend prevalence of 80% in CpT) 59 , 60 .…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Interestingly, these taxa are commonly found in patients with CRC 57 , with the Fusobacterium genus frequently being associated with tumor progression 58 . Moreover, CpT samples possessed microbial genera commonly involved in development of intestinal disease or pathologies, such as Streptococcus (taxonomic trend prevalence of 80.00% in CpT) and Gemella (taxonomic trend prevalence of 80% in CpT) 59 , 60 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, detection of diarrheagenic E. coli strains are much lower when examining stool from patients in developed countries, highlighting their common frequency in sanitation poor settings [19]. Even in asymptomatic individuals, prevalence of diarrheagenic strains of E. coli are high in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Clostridioides difficile was the most common pathogen identified in these studies, and less expensive testing is available to test for C. difficile alone. 39 41 There are some limitations with using GI PCR panels in neutropenic patients, including some notable gaps in the current panels available, such as Strongyloides stercoralis , cytomegalovirus, and certain strains of adenovirus. 42 In addition, these tests do not differentiate colonization from active infection; thus, detection of an organism on the PCR panel does not rule out non-infectious etiologies like GVHD.…”
Section: Updates In Diagnosismentioning
confidence: 99%
“…37,38 A few studies have evaluated the use of the GI PCR panels in cancer patients. 29,[39][40][41] Results from the studies comparing the GI PCR panels to conventional testing in this population demonstrated significantly improved pathogen identification. 29,40,41 It is unclear how many patients were presenting with FN or how the GI PCR panels influenced clinical outcomes in these studies, but they highlight the ability of these tests to improve diagnosis of infectious diarrhea in cancer patients.…”
Section: Pcr-based Testsmentioning
confidence: 99%
See 1 more Smart Citation